Comparative literature under a different heading (Colloquia Comparativa Litterarum, 2025)
This article discusses Ian Bostridge’s book Schubert’s Winter Journey: Anatomy of an Obsession, which – beyond the label of musicological research dedicated to Franz Schubert’s song cycle “Winterreise” (“Winter Journey”), a masterpiece of Romanticism that was based on poems by Wilhelm Müller – stands out with its remarkable achievements in the field of comparative literature and calls attention to the contemporary state of this academic discipline.
Keywords: Ian Bostridge; Schubert’s Winter Journey: Anatomy of an Obsession; Franz Schubert; Wilhelm Müller; Comparative literature